Implementation of healthy school strategies. An intersector alliance - Cárdenas Cárdenas, Luz Mery; Suárez Cárdenas, Carmen Constanza; Agudelo Cely, Nancy Aurora (Investigación y Educación en Enfermería, 2010)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> Objective. To evaluate the implementation of healthy school strategies in a primary school institution in the rural area of Nuevo Colon (Boyacá) in Colombia. Methodology. Unique case study with two stages, a diagnostic one and an intervention one. In the diagnostic stage a cross sectional descriptive study was performed to determine scholars health status, the situation found was supplemented with a community self diagnosis. The intervention stage was framed into two fields of action: with the educational community members and form the inter sector and inter institution perspective. Results. Environment problems related with the location of the institutions and unfavorable situations in the scholars, both at the familiar and individual level were identified. Alternative solutions to the problems searched through community participation, health education and building alliances between the educational community, health field, education and municipal authorities. Conclusion. Healthy school strategies contributed to the improvement of scholars’ quality of life and human development.